The life of joy Philippians ; v. 1 - Lloyd-Jones, David Martyn, 1899-1981 (London, UK Hodder and Stoughton, 1989)
Contents : v. 1 : Philippians chapter 1 and 2
Keywords: Bible. N.T. Philippians I-II -- criticism and interpretation